Distance Students’ Readiness for Social Media and Collaboration - Poellhuber, Bruno; Anderson, Terry; Roy, Normand (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
In recent years, there has been a rapid growth in the use of social networking tools (e.g., Facebook) and social media in general, mainly for social purposes (Smith, Salaway & Caruso 2009). Many educators, including ourselves, believe that these tools offer new educational affordances and avenues for students to interact with each other and with their teachers or tutors. Considering the traditional drop-out rate problem documented in distance courses (Rovai, 2003; Woodley, 2004), these tools may be of special interest for distance education institutions as they have potential to assist in the critical “social integration” associated with persistence (Sweet, 1986; Tinto, 1975). However, as distance students are typically older than regular on-campus students, (Bean & Metzner, 1985; Rovai, 2003) little is known about their expertise with social media or their interest in harnessing these tools for informal learning or collaborating with peers. To investigate these issues, an online questionnaire was distributed to students from four large Canadian distance education institutions. A systematic sampling procedure lead to 3462 completed questionnaires. The results show that students have diverse views and experiences, but they also show strong and significant age and gender differences in a variety of measures, as well as an important institution effect for interest in collaboration. Males and younger students score higher on almost all indicators, including cooperative preferences. The limits of the study and future developments and research questions are outlined.